Employee incentives, goal and performance and motivation towards job satisfaction in Bermaz Motor Group (BMG), Mazda, Shah Alam / Khairina Kamarulzaman - Kamarulzaman, Khairina (Faculty of Business and Management, 2010)
This study is about the employee incentives, goal and performance and motivation towards job satisfaction. It studies about the employee job satisfaction in Bermaz Motor Group (BMG). It will cover three main ideas which are incentives, goal and performance. The objectives of this study are to determine what the incentives are offered by Bermaz Motor Group to their employees, to identify whether the employee are clear about the goals and performance set by BMG and to examine efforts made by BMG in motivating the employees. This research will use the probability sampling. The employees in operation level such workshop department faced a problem regarding incentive given by the company. They are not satisfied with the incentives given such bonuses are not sufficient. In terms of salary, the basic pay offered to the employees has different for the same position. The experiences and the different level of certificate have being the factors of the differences for the base pay. This situation has make some of the employees has not satisfy in how the company has categorize their workers based on this two factors. Their ability and credibility has been measure based on the experience even though they set for the same position. The result shows that all the employees’ incentives, goal and performance and motivation will influence to job satisfaction.